2011
DOI: 10.3858/emm.2011.43.8.051
|View full text |Cite|
|
Sign up to set email alerts
|

TiO2nanotube stimulate chondrogenic differentiation of limb mesenchymal cells by modulating focal activity

Abstract: Vertically aligned, laterally spaced nanoscale titanium nanotubes were grown on a titanium surface by anodization, and the growth of chondroprogenitors on the resulting surfaces was investigated. Surfaces bearing nanotubes of 70 to 100 nm in diameter were found to trigger the morphological transition to a cortical actin pattern and rounded cell shape (both indicative of chondrocytic differentiation), as well as the up-regulation of type II collagen and integrin β4 protein expression through the down-regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…This correlation between the anodization potential and the cell proliferation is mostly associated with the NT diameter. According to the literature, smaller diameter NTs lead to higher cell proliferation. In our work, NTs obtained at 30 V anodization had an inner diameter of ∼40 nm, whereas the NTs obtained at 60 V had a pore diameter of ∼100 nm for all substrates. As a result, the highest proliferation of hMSCs was observed for NTs obtained at 30 V anodization.…”
Section: Resultssupporting
confidence: 48%
See 2 more Smart Citations
“…This correlation between the anodization potential and the cell proliferation is mostly associated with the NT diameter. According to the literature, smaller diameter NTs lead to higher cell proliferation. In our work, NTs obtained at 30 V anodization had an inner diameter of ∼40 nm, whereas the NTs obtained at 60 V had a pore diameter of ∼100 nm for all substrates. As a result, the highest proliferation of hMSCs was observed for NTs obtained at 30 V anodization.…”
Section: Resultssupporting
confidence: 48%
“…Additionally, it is vital to evaluate the influence of TiO 2 NTs and the anodization voltage, which is responsible for tube morphology, on the cell adhesion and proliferation. NTs have been widely explored for use as cell culture substrates in tissue engineering applications due to their mechanical, electrical, and optical properties . The biological performance of Ti–Nb substrates with and without deposition of NTs was evaluated via the assessment of hMSC adhesion and proliferation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, by controlling macrophage cell response it is possible to enhance the healing process, by promoting a reparative rather than a chronic inflammatory response [176] at bone/dental implants. Furthermore, it has been shown that cell adhesion, migration and proliferation are higher with TNTs between 15nm and 30 nm diameter [177][178][179][180], whereas cell apoptosis is induced with TNTs diameters between 50nm to 100nm [14, 177,180,181]. However, contradictory results have been reported by other studies [172,[182][183][184] demonstrating that TNTs with diameters between 80nm to 470nm increase cell adhesion, migration and cell proliferation without inducing apoptosis.…”
Section: Optimizing Biological Cqa With Tntsmentioning
confidence: 99%
“…This cell adhesion event, significantly enhanced in the nanofibrous scaffolds, can alter the subsequent cellular behaviors such as increased cell spreading and early differentiation, which has been reported to be detrimental to the maintenance of the chondrogenic phenotypes. 29,3739…”
Section: Resultsmentioning
confidence: 99%